Pharmacokinetics and pharmacodynamics of Abelacimab (MAA868), a novel dual inhibitor of Factor XI and Factor XIa. (19th November 2021) - Yi, B. Alexander; Freedholm, Debra; Widener, Nancy; Wang, Xiaohui; Simard, Emilie; Cullen, Constance; Al‐Saady, Naab M.; Lepor, Norman E.; Coulter, Sara; Lovern, Mark; Bloomfield, Dan
Abstract: Background: Factor XI (FXI) inhibition offers the promise of hemostasis‐sparing anticoagulation for the prevention and treatment of thromboembolic events. Abelacimab (MAA868) is a novel fully human monoclonal antibody that targets the catalytic domain and has dual activity against the inactive zymogen Factor XI and the activated FXI. Objectives: To investigate the safety, pharmacokinetics (PK), and pharmacodynamics (PD) of single dose intravenous and multiple dose subcutaneous administration of abelacimab in healthy volunteers and patients with atrial fibrillation, respectively. Patients/Methods: In study ANT‐003, healthy volunteers were administered single intravenous doses of abelacimab (30–150 mg) or placebo. The ANT‐003 study also included a cohort of obese but otherwise healthy subjects. In study ANT‐004, patients with atrial fibrillation were administered monthly subcutaneous doses of abelacimab (120 mg and 180 mg), or placebo, for 3 months. Key PK and PD parameters, including activated partial thromboplastin time (aPTT) and free FXI levels, as well as anti‐drug antibodies (ADA) were assessed. Results: Following intravenous administration of abelacimab, the terminal elimination half‐life ranged from 25 to 30 days. One hour after the start of the intravenous infusion greater than 99% reductions in free FXI levels were observed. Following once monthly subcutaneous administration, marked reductions from baseline in free FXI levels were sustained. Parenteral administration of abelacimab demonstrated a favorable safety profile with no clinically relevant bleeding events. Conclusions: Intravenous and multiple subcutaneous dose administration of abelacimab were safe and well tolerated. The safety, PK, and PD data from these studies support the clinical development of abelacimab.